(untitled) - Graham, Ian S. (New York, 1999)
The book provides a complete explanation of XML structure, syntax, and rules, built around detailed examples; a comprehensive specification guide to XML; in-depth coverage of namespaces ans schemas; a detailed dicussion of the Unicode character sets and their relationship to XML; a detailed glossary of important XML terms; and a quick-reference guide to XML features, with illustrated examples of how they differ from HTML.
Keywords: XML ( document markup language )